Field study 3 : technology in the learning environment - Salana, June P. (Manila, Philippines : Rex Book Store, 2013)
This course is designed to enrich the students' experiences in developing and utilizing appropriate technology to facilitate learning.
Students' Expected Outcomes 1 -- Learning Through Technology 2 -- Activity -- New Ways of Learning Using Technology 27 -- Activity -- Problem-solving 35 -- Activity -- Technology that enhances verbal-linguistics intelligence 40 -- Activity -- Patterning 65 -- Pattern blocks 65 -- Activity -- Task card puzzles 69 -- Activity -- Junk drawer manipulatives 71 -- Activity -- References 73
Includes bibliographical references.
Keywords: TEACHING TECHNOLOGY